In vivo study of the antioxidant test of ethanolic extract of Chromolaena odorata Linn. leaves - Solihah, Indah; Herlina, Herlina; Munawwaroh, Inayatul; Rasyid, Riana Sari Puspita (MEDISAINS, 2020)
Background: Chromolaena odorata L. leaf was reported to contain phenolic group compounds, such as flavonoids. Flavonoid compounds have been reported to have antioxidant activity. Based on in vitro study, Chromolaena odorata L. leaves have potent antioxidant activity. However, in vivo, studies with dose variations have not been reported.Purpose: This study evaluates the antioxidant activity with various doses of ethanolic extract of Chromolaena odorata L. leaves against male Wistar rats induced by paracetamol.Methods: Flavonoid contents were measured spectrophotometrically based on the formation of a complex flavonoid-aluminum. Quercetin was used to make a calibration curve. In vivo test was used TBARS method carried out by measured malondialdehyde (MDA) level in male Wistar rats induced by paracetamol 2g/Kg BW. The test was carried out on extracts with doses of 125, 250, and 500 mg/Kg BW. Vitamin C with dose 6,5mg/Kg BW used as a positive control, and 1% of Na CMC used as the negative control. Histopathology assessment of liver used Hema-toxylin Eosin Stain.Results: Ethanolic extract of Chromolaena odorata L. leaves contain flavonoid 126.459±0.163 mg/g extract as quercetin equivalent. Intoxication paracetamol on rats increased MDA serum level significantly different (p-value < 0.005) with normal control. Treatment of ascorbic acid and extracts decreased MDA serum level significantly different (p-value < 0.005) with control negative and improved the histological structure of hepatocytes.Conclusion: Ethanolic extract of Chromolaena odorata Linn. dose 500 mg/Kg BW was the best treatment with exhibited 58.974% reduction of MDA serum level and better improve the histological structure hepatocytes than other doses